Diseminasi Teknologi Budidaya Yumina Bumina Ikan Herbivora Mendukung Ketahanan Pangan Masyarakat Desa Cisaladah Kecamatan Cigombong Kabupaten Bogor, Jawa Barat - Ade Sunaryo; Yenni Nuraini (Unri Conference Series: Community Engagement, 2021)
Dissemination is one form of activity to obtain information aimed at individuals or target groups who meet the qualifications. This activity aims to apply the dissemination of aquaculture technology with community nutrition self-help activities through side dishes and vegetables produced from the Yumina-Bumina fish farming method. In addition, the existence of Yumina-Bumina cultivation technology is expected to provide convenience for the community, especially stunting areas, to increase their livelihoods by carrying out fish cultivation activities that do not require a large place and a lot of water. This activity was carried out in three groups of fish farmers in Cisaladah Village, Cigombong District, Bogor Regency. The stages of activities carried out in community service activities include socialization, training and mentoring. The dissemination activities of Yumina-Bumina aquaculture technology products to the community that have been carried out have been carried out thanks to the collaboration of the service team, village officials and fish cultivator groups in creating and developing a productive herbivorous fish farming business, so as to encourage community economic improvement